1979
DOI: 10.1002/hlca.19790620446
|View full text |Cite
|
Sign up to set email alerts
|

Propellanes. L. Further support for control by secondary orbital overlap during Diels‐Alder reactions of certain propellanes,

Abstract: In contrast to the behavior of 4‐substituted‐1,2, 4‐triazoline‐3, 5‐diones which add to the syn‐face of the cyclohexadiene with respect to the hetero‐ring in propellanes of type 1, dienophiles containing a C, C double bond instead of an N, N double bond add exclusively to the anti‐face of the same substrates. This supports our thesis that these reactions are controlled by secondary orbital interaction between the N, N dienophiles and the hetero‐ring of the substrates, an interaction which cannot exist in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, this rationalization is not ap-plicable to either N-phenylmaleimide or maleic anhydride, and thus the facial selectivity is reversed (entry 11) upon changing the dienophile. 13 In addition, as entries 13 and 14 indicate, the presence of neighboring carbonyl groups and double bonds also influence the selectivity. On the basis of electrostatic interactions Kahn and Hehre concluded that electrophilic dienophiles should add preferentially to the more nucleophilic diene face, syn to "a lone-pair-containiñg allylic substituent".33 Clearly this simple electrostatic model cannot be extended in a straightforward manner to sulfur systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this rationalization is not ap-plicable to either N-phenylmaleimide or maleic anhydride, and thus the facial selectivity is reversed (entry 11) upon changing the dienophile. 13 In addition, as entries 13 and 14 indicate, the presence of neighboring carbonyl groups and double bonds also influence the selectivity. On the basis of electrostatic interactions Kahn and Hehre concluded that electrophilic dienophiles should add preferentially to the more nucleophilic diene face, syn to "a lone-pair-containiñg allylic substituent".33 Clearly this simple electrostatic model cannot be extended in a straightforward manner to sulfur systems.…”
Section: Discussionmentioning
confidence: 99%
“…NMR (300 MHz, CDC13) 7.S-7.3 (m, 3 ), 7.05 (d, 2 H, J = 7.5 Hz), 3.35 (s, 2 ), 1.63 (s, 6 ), 1.42 (s, 6 ), 1.30 (s, 1 H), 1.13 (s, 3 H); 13C NMR (CDClj) 176.4, 135.1, 131.9, 129.1, 128.4, 126.5, 75.3, 61.1, 51.6, 20.5, 11.7; MS caled for C^H^NSOz 341.1449341. , found 341.14382 petroleum ether/EtOAc) gave the anti adduct 15 (0.136 g, 40%): mp 122-123 °C (ether-hexane); IR (CHCI3) 2963,2929,1769,1709,1598,1499,1455,1378,1306,1173,1 168, 1085 cm'1; NMR (300 MHz, CDC13) 7.45-7.35 (m, 3 H), 7.05 (d, J = 7.2 Hz, 2 ), 3.10 (s, 2 ), 1.61 (s, 6 ), 1.49 (s, 6 H), 1.20 (s, 1 ), 1.14 (s, 3 H); 13C NMR (CDC13) 176.0, 137.6, 131.9, 129.2, 128.5, 126.5;MS caled for C20H23NSO2 341.1449, found 341.1438 Cycloaddition of 5-Hydroxy-l,2,3,4,5-pentamethylcyclopen tad lene (13) with Maleic Anhydride. Anhydrous MeOH (20 mL) was distilled into a flask containing the sulfoxide 10 (1.185 g, 5.98 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…When -lXl=lq-in the dienophile is replaced by -CH=CH-(II) the attack will take place on the face anti to the hetero-ring (Kaftory, Peled & Ginsburg, 1979;Kaftory, 1980, molecule b).…”
Section: Introductionmentioning
confidence: 99%